Baltic Cluster Report : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues paper focuses on the Baltic model, Baltic-Nordic links, and convergence. The Baltic countries form a distinct group within a tightly integrated Nordic-Baltic region. They are following similar approaches to economic policy, broadly in line with those of Northern European and the Anglo-Saxon countries. Their macroeconomic policies are generally robust. The paper examines the possible causes of the creditless recoveries in the Baltic countries. It characterizes their experience in comparison with other episodes of creditless recoveries in both advanced and emerging market economies, and also investigates demand and supply constraints to credit expansion in the Baltics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet